A Python Package to Preprocess the Data Produced by Novonix High-Precision Battery-Testers. Issue 1 (4th March 2020) - Gonzalez-Perez, V.; Keil, P.; Li, Y.; Zülke, A.; Burrel, R.; Csala, D.; Hoster, H.
We presentpreparenovonix, a Python package that handles common issues encountered in data files generated with a range of software versions from the Novonix battery-testers.1 This package can also add extra information that makes easier coulombic counting and relating a measurement to the experimental protocol. The package provides a master function that can run at once the cleaning and adding derived information, with flexibility to choose only some features. There is a separate function to simply read a column by its given name. The usage of all the functions is documented in the code including examples. The code presented here can be installed either as a python package2 or from a GitHub repository.3